School ethnic-racial socialization and critical action among Black youth - Kubi, Gabrielle; Byrd, Christy M.; Diemer, Matthew A. (Frontiers in Education, 2022)
We explore the interaction of different types of school ethnic-racial socialization, youth’s perceptions of the messages that schools and their agents broadcast about race and ethnicity, as it shapes Black youth’s critical action, the individual and collective action that youth engage in to combat oppression and racism. In particular, the co-occurence of critical consciousness socialization (emphasizes racial inequity; CCS), cultural socialization (celebrates youth’s culture/s; CS), and color evasive socialization (de-emphasizes and thus delegitimizes the importance of race; CES) are explored. The adaptive culture and Mustaffa’s conceptualization of Black life-making, an aspect of freedom dreaming in which Black people define and care for themselves in ways that counter dominant, anti-Black ideologies (such as critical action), serve as the overarching theoretical frameworks. As both the adaptive culture paradigm and critical action necessitate a target of resistance, we hypothesize that CES, in providing Black youth something to implicitly resist against, may actually serve as a positive moderator between CCS and/or CS and their critical action. We investigate these questions among a sample of Black adolescents (n = 285, M = 15.09 years, SD = 1.38 years). Benjamini-Hochberg corrected hierarchical moderations with age as a covariate and socialization type and interaction between types as predictors revealed that the interaction between CCS and CES significantly predicted critically conscious action (β = 0.25, SE = 0.08, t(193) = 2.54, p < .05) and political anti-racist action (β = 0.21, SE = 0.09, t(193) = 2.38, p < .05). Critically conscious action was more frequent among Black youth who perceived greater CES. The relationship between CCS and political anti-racist action was stronger among those who perceived greater CES. These findings may provide comfort to those worried about CES’ impact. Black youth simultaneously socialized with CCS seem to develop a critical consciousness that allows them to trouble CES and to be critically active despite it. Engaging in varied, frequent critical action allows Black youth to continue the life-making which improves the Black American experience and drives their freedom dreaming.